Characteristics of pregnant women with diabetes using injectable glucose-lowering drugs in the EVOLVE study. (12th December 2022) - Mathiesen, Elisabeth R.; Ali, Norsiah; Anastasiou, Eleni; Cypryk, Katarzyna; de Valk, Harold W.; Dores, Jorge M.; Dunne, Fidelma P.; Ekelund, Magnus; Durán García, Santiago; Hanaire, Hélène; Husemoen, Lise Lotte N.; Ivanisevic, Marina; et al.
Abstract: Aims: To examine clinical parameters, glycemic control, folic acid supplementation, and the presence of other chronic diseases during early pregnancy in the EVOLVE study population (women with pre-existing diabetes treated with injectable glucose-lowering drugs). Methods: Cross-sectional baseline evaluation of EVOLVE: an international, multicenter, non-interventional study investigating the safety of injectable glucose-lowering drugs in pregnant women with pre-existing type 1 (T1D) or type 2 diabetes (T2D). Data were collected at enrollment visit interviews before gestational week 16. Results: In total, 2383 women from 17 mainly European countries were enrolled in the study: 2122 with T1D and 261 with T2D; mean age was 31 and 33 years, and duration of diabetes was 15 and 6 years, respectively. For women with T1D or T2D, 63% and 75%, respectively, received basal and rapid-acting insulin, 36% and 3% rapid-acting insulin only, 0.7% and 14.0% basal insulin only, 0.2% and 5.4% premix insulin, 0.0% and 1.2% injectable glucagon-like peptide-1 receptor agonist treatment without insulin. In women with T1D or T2D, respectively, during early pregnancy, 59% and 62% had HbA1c <7.0% (53 mmol/mol); 16% and 36% reported not taking folic acid before or during early pregnancy. Overall, >40% of women had ≥1 chronic concomitant condition (predominantly thyroid disease or hypertension). Retinopathy was the most commonly reported diabetic complication. The most commonly reported previous pregnancy complication was miscarriage. Conclusions: Baseline data from this large multinational population of women with pre-existing diabetes indicate that sub-optimal glycemic control, poor pregnancy planning, and chronic concomitant conditions were common in early pregnancy.